2015
DOI: 10.1167/iovs.14-15334
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Retinal Function and Morphology in Aging Ccl2 Knockout Mice

Abstract: These data show that Ccl2 is important for preserving RPE and glial morphology with age, yet retinal function and gross morphology are maintained. Altered signaling in this chemokine pathway may, however, increase RPE and retinal vulnerability to disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 63 publications
1
30
0
Order By: Relevance
“…32 The 7-day time point was chosen, as previous work has identified that the RPE areas selectively ablated by the nanosecond laser are retiled by this time, 29 while the 90-day time point was chosen to assess for a delayed neovascular response. The cornea of mice was anesthetized with topical Alcaine (0.5%) and the pupils dilated with atropine (1%) and phenylephrine (10%).…”
Section: Fundus Photography and Fluorescein Angiographymentioning
confidence: 99%
See 1 more Smart Citation
“…32 The 7-day time point was chosen, as previous work has identified that the RPE areas selectively ablated by the nanosecond laser are retiled by this time, 29 while the 90-day time point was chosen to assess for a delayed neovascular response. The cornea of mice was anesthetized with topical Alcaine (0.5%) and the pupils dilated with atropine (1%) and phenylephrine (10%).…”
Section: Fundus Photography and Fluorescein Angiographymentioning
confidence: 99%
“…The posterior eyecups (n ‡ 5 per experimental group) were fixed in 4% paraformaldehyde in 0.1 M phosphate buffer, pH 7.4 (PB) for 30 minutes and cryoprotected in graded sucrose (10%, 20%, 30%) in PB overnight. 33 For retinal wholemounts, the entire eyecup (retina/choroid/sclera) was processed for immunohistochemistry as described previously 32,34 and specifically below. For retinal sections, the eyecup was embedded in optimal cutting temperature (OCT) compound (Tissue-Tek; Sakura, Torrance, CA, USA), frozen at À208C, and sectioned transversely at 14 lm on a Microm HM550 cryostat (Thermo Scientific, Walldorf, Germany).…”
Section: Immunohistochemistry and Confocal Microscopymentioning
confidence: 99%
“…Ambati et al (Ambati et al, 2003) firstly mentioned that mice deficient in MCP-1 develop cardinal features of AMD, including accumulation of lipofuscin and drusen, photoreceptor atrophy and CNV invation. Vessey et al (Vessey et al, 2015) also showed that MCP-1 is important for preserving RPE and glial (C) Activation of ERK1/2, p38, JNK1/2 and NF-kB induced by 7378 K light at 4 h was significantly suppressed by vitamin C and NAC treatment. Results of are presented as means ± SD (n ¼ 3, *P < 0.05; **P < 0.01; ***P < 0.001 compared with group treated with 7378 K light alone).…”
Section: Discussionmentioning
confidence: 96%
“…As the most important pro-inflammatory chemokines in CXC and CC families, IL-8 and MCP-1 are potent chemoattractants of neutrophils and monocytes, respectively (Baggiolini and Clark-Lewis, 1992;Douglas et al, 1997). A large amount of studies have demonstrated that disrupted expression of these pathological cytokines are correlated with the development of AMD (Ambati et al, 2003;Cascella et al, 2014;Jonas et al, 2012;Pons and Marin-Castano, 2011;Roh et al, 2009;Vessey et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…One of the more prominent features that occurs in retinae with age is the accumulation of cells of the innate immune system within the subretinal space . As shown in Figure , immune cells accumulate around some of the lesions associated with AMD, especially reticular pseudodrusen, and have also been reported in association with atrophic areas in retinae with geographic atrophy and or choroidal neovascularisation …”
Section: Changes In Mononuclear Phagocytes In Age Related Macular Degmentioning
confidence: 99%